Polish Provinces as E-Regions in Comparison with the European Union - Wojnicka, Elżbieta (Regional Barometer. Analyses & Prognoses, 2011)
In the paper the position of Polish regions in comparison with countries and regions of the EU which are the most advanced in creation of e-economy was presented. Moreover, to the article the term 'e-region', that is a region exceeding 4% of high technology services in general employment, was introduced. These regions constitute 12,7% of NUTS 2 UE 27 regions, among them there is the Mazowieckie Voivodship. Carried out research showed strong correlation between the GDP rate per inhabitant and the development of high technology services in the region and negative correlation between the development of high technology services and the participation of agriculture in employment.